Autonomously Folding Protein Fragments Reveal Differences in the Energy Landscapes of Homologous RNases H - Rosen, Laura E.; Marqusee, Susan (PLOS ONE, 2015)
An important approach to understanding how a protein sequence encodes its energy landscape is to compare proteins with different sequences that fold to the same general native structure. In this work, we compare E. coli and T. thermophilus homologs of the protein RNase H. Using protein fragments, we create equilibrium mimics of two different potential partially-folded intermediates (Icore and Icore+1) hypothesized to be present on the energy landscapes of these two proteins. We observe that both T. thermophilus RNase H (ttRNH) fragments are folded and have distinct stabilities, indicating that both regions are capable of autonomous folding and that both intermediates are present as local minima on the ttRNH energy landscape. In contrast, the two E. coli RNase H (ecRNH) fragments have very similar stabilities, suggesting that the presence of additional residues in the Icore+1 fragment does not affect the folding or structure as compared to Icore. NMR experiments provide additional evidence that only the Icore intermediate is populated by ecRNH. This is one of the biggest differences that has been observed between the energy landscapes of these two proteins. Additionally, we used a FRET experiment in the background of full-length ttRNH to specifically monitor the formation of the Icore+1 intermediate. We determine that the ttRNH Icore+1 intermediate is likely the intermediate populated prior to the rate-limiting barrier to global folding, in contrast to E. coli RNase H for which Icore is the folding intermediate. This result provides new insight into the nature of the rate-limiting barrier for the folding of RNase H.